Fundamental food microbiology. - Ray, Bibek, 1935-; Bhunia, Arun, ....- (Boca Raton : CRC, 2008)
Maintaining the high standard set by the previous bestselling editions, Fundamental Food Microbiology, Fourth Edition presents the most up-to-date information in this rapidly growing and highly dynamic field. Revised and expanded to reflect recent advances, this edition broadens coverage of foodborne diseases to include many new and emerging pathogens, as well as descriptions of the mechanism of pathogenesis. An entirely new chapter on detection methods appears with evaluations of advanced rapid detection techniques using biosensors and nanotechnology. With the inclusion of many more easy-to-follow figures and illustrations, this text provides a comprehensive introductory source for undergraduates, as well as a valuable reference for graduate level and working professionals in food microbiology or food safety. Each chapter within the text's seven sections contains an introduction as well as a conclusion, references, and questions. Beginning with the history and development of the field, Part I discusses the characteristics and sources of predominant food microorgasnisms and their significance. Part II introduces microbial foodborne diseases, their growth and influencing factors, metabolism, and sporulation. The third Part explains the beneficial uses of microorganisms in starter cultures, biopreservation, bioprocessing, and probiotics. Part IV deals with food spoilage and methods of detection, followed by a discussion in Part V of foodborne pathogens associated with intoxication, infections, and toxicoinfections. Part VI reviews control methods with chapters on control of microbial access and removal by heat, organic acids, physical means, and combinations of methods. The final section is an in-depth look at advanced and traditional methods of microbial detection and food safety. Four appendices provide additional details on food equipment and surfaces, predictive modeling, regulatory agencies, and hazard analysis critical control points.
Keywords: Microbiologie; Voeding